PRIME: Pragmatic Interoperability Architecture to Support Collaborative Development of Scientific Workflows - Neiva, Frâncila Weidt; David, José Maria N.; Braga, Regina; Campos, Fernanda; Freitas, Vitor (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2015)
Providing interoperability support across applications only considering the format and meaning (i.e. Syntax and semantic) in data exchange is not enough to achieve an effective and meaningful collaboration. Therefore, pragmatic interoperability has been pointed out as a key requirement to foster collaboration in distributed environment. However, fulfilling this requirement is not a trivial task. The aim of this study is to propose and evaluate pragmatic interoperability architecture to support collaborative development of scientific workflows in the context of ECOS Collaborative PL-Science infrastructure, where pragmatic interoperability has been investigated.